Challenges of digital technologies for Albanian manufacturers (Case studies) - GJIKA, Ira; GJIKA, Ira; PANO, Nikollaq; SKENDAJ, Elton (Edelweiss Applied Science and Technology, 2024)
This paper investigates how Albanian manufacturing companies use information systems in their managerial processes and ways to promote their innovative use. There are evidence Albanian manufacturing companies use advanced production technologies and are increasing application of information systems. Still, there is a lack of knowledge and literature about the magnitude of information systems used in Albanian small and medium enterprises (SMEs) and their integration into the company’s activity. This study intends to reveal the usage of information systems in core activities of SMEs, the benefits these systems bring to the management and performance of companies, and the driving factors to deploy these systems. The study was conducted using mixed research methodology. It has combined secondary research to create the theoretical context of the observation with primary research in the form of case studies applied in some manufacturing companies. The paper brings findings on the extent of information systems used in SMEs and impact on companies’ management and performance. The conclusions point out the barriers and challenges companies face in applying systems and emphasize some ways to overcome them. The practical implications of this work are that these findings and recommendations apply to the cases observed and many other SMEs in the manufacturing industry. The dissemination of such knowledge would encourage Albanian businesses to promote innovation and digitization.